Color Editing and 3D Volume Rendering of OCT-angiography Images. Issue 1 (2017) - El Ameen, Ala'a; Querques, Giuseppe; Semoun, Oudy; Souied, Eric H.
Purpose: To describe an innovative imaging technique of color editing and 3D volume rendering of optical coherence tomography-angiography (OCT-A) images. Methods: Each vascular layer acquired by OCT-A (AngioVue, Optovue) is colored and edited with the GNU Image Manipulation Program. Then a 3D volume rendering of the assessed retinal area is possible, using Adobe After Effect software (Adobe Systems). Results: The combined color editing and 3D volume rendering of optical coherence tomography angiography images allow the creation of a short movie displaying the 3D image from chosen angles. Conclusions: Image editing and 3D volume rendering is a rather simple technique, which, besides its aesthetic prerequisites, also facilitates simultaneous, distinct visualization of the segmented retinal layers.